Fifty Years of the Chilean Agrarian Reform: From the Protection to the Violation of Peasants' Rights - Castañeda Meneses, Patricia (2018)
This article was written on the occasion of the 50-year commemoration of the Chilean agrarian reform. It aims to analyze the processes of agrarian reform and counter-reform, from the perspective of the protection of peasants' rights. These rights related to access to land, technical assistance, agricultural preferential credit, and marketing, as well as the right of association of agricultural workers. They included the social rights to education, health and housing. Compliance with these rights was assumed by state agencies and materialized in a constitutional reform and in legal bodies that formalized the process and gave it viability as a state policy. Public agencies were created to support the redistribution of land ownership, public resources were assigned from the national budget, and intersectoral actions were taken in favor of this important social group. Ever since the coup d’état of 1973, a process of agrarian counter-reform started, and progressively violated the peasants' rights. The land was given out on an individual basis, without technical state support or preferential access to agricultural credit, and the actions aiming at ensuring social rights were abandoned. As a result, it is estimated that more than 50% of the allocated land to peasants was sold, creating a market of agricultural land and rural labor that is the base of the current Chilean agro-exporting capitalism.